2018
DOI: 10.21776/ub.jepa.2018.002.05.5
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kinerja Daya Saing Industri Teh Indonesia

Abstract: This study aims to measure and analyze the competitiveness of Indonesian tea industry in the world based on the performance of international trade. There are four steps taken continuously to achieve the objective. First, measuring the competitiveness of Indonesian tea industry with Relative Trade Advantage (RTA). Second, identifying the major factors impacting on competitive performance by conducting surveys to tea industry stakeholders. Third, analyzing the determinants of competitiveness of the tea industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the ASEAN market, Indonesian tea also has strong competitiveness with an RCA value of 2.89 (Satryana & Karmini, 2016). Other research that uses a different analytical tool, namely Relative Trade Advantage (RTA) also shows the same results where Indonesian tea has competitiveness compared to other domestic commodities (RTA>1) (Nurohman et al, 2018). However, even so, the position of competitiveness of Indonesian tea is still inferior to that of Sri Lanka, Kenya, and India (Zakariyah et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 75%
See 1 more Smart Citation
“…In the ASEAN market, Indonesian tea also has strong competitiveness with an RCA value of 2.89 (Satryana & Karmini, 2016). Other research that uses a different analytical tool, namely Relative Trade Advantage (RTA) also shows the same results where Indonesian tea has competitiveness compared to other domestic commodities (RTA>1) (Nurohman et al, 2018). However, even so, the position of competitiveness of Indonesian tea is still inferior to that of Sri Lanka, Kenya, and India (Zakariyah et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 75%
“…The number of exports to Russia has increased after showing a downward trend from 2016 to 2019. The decline in Indonesian tea exports to the European region was influenced by regulations restricting the entry of tea related to the rules for limiting pesticide residues in tea (Nurohman et al, 2018). This condition caused in 2018 and 2019 the number of Indonesian tea exports to Malaysia was greater than to Russia (Figure 2).…”
Section: Overview Of Indonesian Tea Exportsmentioning
confidence: 99%
“…The level of competitiveness of tea in 2010 and 2016 showed a high competitive value when compared to other domestic commodities, where the factors that support the competitiveness of the tea industry are the development of the agro-tourism industry and tea ready-to-eat beverage companies (Djohar, 2018). However, at the international level, the results of research conducted by Zakariya et, al (Zakariya et al, 2012) found that the competitiveness of Indonesian tea is relatively lower than Kenya, Sri Lanka, India but still higher than China while competitively showing that Indonesian tea commodities have strong competitiveness because internal and external factors in tea production are >>> Program Studi Ilmu Politik FISIP Universitas 17 Agustus 1945 Jakarta <<< readily available.…”
Section: >>> Program Studi Ilmu Politik Fisip Universitas 17 Agustus ...mentioning
confidence: 99%